PENYELESAIAN SENGKETA TANAH WAKAF MELALUI METODE ALTERNATIF (STUDI KASUS PENUTUPAN AKSES MASJID DI KOJA) - Amara, Nouna Shaina (Jurnal Ilmiah Dinamika Hukum, 2025)
In Indonesia, waqf generally takes the form of land that is used for mosques, prayer rooms, schools, cemeteries and homes for orphans, although the object of waqf is not limited to land alone. A clear waqf certificate is important to provide legal certainty regarding the ownership and use of waqf land, because without this certainty, ownership or management disputes could hamper the use of waqf assets for the public interest. Law Number 41 of 2004 concerning Waqf regulates waqf as a concrete effort to deal with waqf problems, but many people have not officially registered waqf land, which has the potential to cause conflict in the future. An example is the case that occurred at the Jami Nurul Islam Mosque, which is located in Koja, North Jakarta, DKI Jakarta, Indonesia. This research will discuss the legal consequences of the absence of a waqf pledge deed and resolving waqf land disputes through alternative methods, using normative legal research Keywords : Waqf, Waqf Disputes, Alternative Methods.